How CARE Tools Are Being Used to Address Brain Injury and Mental Health Struggles With Survivors of Domestic Violence. Issue 1 (January 2022) - Kemble, Hannah; Sucaldito, Ana; Kulow, Emily; Ramirez, Rachel; Hinton, Alice; Glasser, Allison; Wermert, Amy; Nemeth, Julianna M.
Abstract : Introduction: CARE (C onnect, A cknowledge, R espond, and E valuate) is an advocacy framework developed for domestic violence service organization (DVSO) providers to address and accommodate domestic violence (DV) survivors with brain injury and mental health struggles. The CARE tools were designed for use by advocates and include the Just Breathe booklet, the Head Injury education card, and the Invisible Injuries booklet. Objective: The purpose of this study was to report findings on how CARE tools are being used by DVSO providers as well as their impact on DVSO advocacy practice. Methods: Post-CARE retrospective process evaluation online surveys ( n = 60) and focus groups ( n = 10 groups; 57 advocates) were conducted with consenting staff at 5 DVSOs in Ohio who partnered with the state coalition to develop and evaluate CARE, overseen by a university research partner. Rigorous, iterative coding qualitative analysis methods, endorsed by the Centers for Disease Control and Prevention, were used (Cohen's κ = 0.903 [stage 1] and 0.810 [stage 2]). Results: The use of CARE tools has been integral to DVSO providers' implementation of the CARE advocacy framework. DVSO advocates are using CARE tools to C onnect with self, survivors, and other systems; to A cknowledge that head trauma and mental health struggles are common among survivors and that ongoing education and self-care are necessary for advocates. Advocates have been able to provide a more holistic R esponse through accommodation within DVSOs and referral to other providers, often by using the CARE tools, including the Head Injury education card. Conclusion: CARE tools were designed for lay use to address head trauma, strangulation, and mental health struggles with DV survivors and are free for download at the Center on Partner Inflicted Brain Injury website: https://www.odvn.org/brain-injury . More widespread use of these tools by advocates has the potential to improve services for DV survivors and address what have historically been invisible injuries and mental health struggles in the population. Abstract : Supplemental Digital Content is Available in the Text.